Artifact-oriented learning: a theoretical review of the impact of the arts on learning. Issue 1 (2nd January 2023) - Peppler, Kylie; Davis-Soylu, Heidi J.; Dahn, Maggie
Abstract: Traditional reviews of arts education have focused on why the arts are valuable for learning, but the arts' contributions to cross-disciplinary discourse remain undertheorized. In this article, we provide a theoretical review of the arts and learning to suggest a new way of thinking about how the arts contribute to learning across disciplines through a focus on the production of artifacts. Guided by a sociocultural constructionist view on learning, this review brings together research from across the field of arts education to demonstrate the benefit of policies that support the production and engagement of shareable artifacts. Findings are synthesized through what we name an artifact-oriented learning model, which merges constructionism with ecological systems theory. Our review points to two key pathways of learning through the arts (i.e., making and engaging) and suggests the arts support learning that is multimodal and transactive across settings. Thus, we consider arts education policy as part of a sociocultural process that has rippling effects across disciplines for all layers of a social ecology. Given this orientation, implications for researchers and policymakers are discussed to support decision-making and continued inquiry across arts education research and policy.